Pengukuran Kinerja Metode Balanced Scorecard (Studi Kasus Pada Bank Rakyat Indonesia Tbk Branch Office Bengkalis) - Renny Julita; Endang Sri Wahyuni (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to evaluate the performance of Bank Rakyat Indonesia (BRI) Tbk Branch Office Bengkalis by applying the Balanced Scorecard framework, which encompasses four key perspectives: financial, customer, internal business processes, and learning and growth. The topic is considered important because comprehensive performance measurement is essential for ensuring organizational effectiveness and supporting sustainable competitiveness in the banking sector. A descriptive quantitative approach was employed. The financial perspective was assessed using secondary data obtained from BRI’s 2022–2024 Annual Reports and analyzed through CAMEL-based financial ratios. The customer perspective was measured using questionnaires distributed to 383 customers, while the internal business process and learning and growth perspectives were evaluated using questionnaires completed by 60 internal respondents. The findings indicate that BRI Bengkalis Branch achieved an overall Balanced Scorecard score of 86.66, placing its performance in the “excellent” category. Financial performance showed strong results in CAR, NIM, and CR, although the NPM ratio revealed an area requiring improvement. The customer perspective received a total score of 8,153, reflecting very high satisfaction despite the need to enhance service speed. Internal business processes also demonstrated excellent performance, particularly in operational processes and after-sales service. The learning and growth perspective recorded an employee satisfaction level of 89.75, suggesting a supportive and productive work environment. Overall, the study concludes that the Balanced Scorecard is an effective tool for providing a holistic picture of organizational performance and serves as a valuable basis for continuous improvement.